Measurement and simulation validation of numerical model parameters of fresh concrete - Zhang Ke (De Gruyter, 2021)
In the numerical simulation of the macroscopic flow of the concrete, it can optimize the performance indicators of the screw conveyor and improve the uniformity of the material to be discharged in the batch production. The discrete element method is effective. The accuracy of physical parameters of this method is a key issue for the reliability of the simulation results of concrete. In this study, we measured the parameters describing the interaction between gravel, mortar, as well as between these two materials and the wall (steel). The experimentally determined parameters include the particle density, size, shape, coefficient of restitution, coefficients of static, and rolling friction. The cohesion coefficient of mortar particles for batch time was obtained by comparing the spread diameter and flow time in V-funnel experiments and simulation. After these calibration steps, the DEM parameters were validated by comparison of the mass flow rate and driving power by the batch production of screw conveying in simulations and experiments. The calculated results are proved to be close to the experimental data, which demonstrates that the measured DEM parameters are of sufficient accuracy to be used in the simulation of concrete flow performance (mass flow rate, energy consumption) in the screw conveyors.